Evaluation of the Contributions of Vitellaria Paradoxa C. F. Gaertn and Parkia Biglobosa (Jacq.) Benth to Rural Livelihood in Oyo State, Nigeria (2012)
Upsurge in population has resulted in pressure on many tree species including Vitellaria paradoxa C.F.Gaertn.and Parkia biglobosa (Jacq.) Benth. These species are highly valued for their socio economic potentials. The study therefore assessed the contribution of V. paradoxa and P. biglobosa to rural livelihood in Oyo State, Nigeria with a view to generating information on the socio-economic values of the species to the rural communities. Stratified sampling technique was used to divide the study area into three based on ecological zones where twenty percent of each ecological zone was selected. A multistage sampling procedure was employed in collecting data on socio-economic importance of the two species using structured questionnaire. Data collected were analyzed using descriptive statistics, cross tabulation and chi-square. The result of chi-square analysis revealed that degree of contributions of the species to daily income of processors, marketers and harvesters were significant (P < 0.05) in dry woodland and moist woodland but not significant in the rainforest zone. The degree of contribution of V. paradoxa to household food consumption was not significant in moist woodland and rainforest but significant in dry woodland (P < 0.05). It is recommended that domestication and plantation establishment of the two species should be encouraged by the forestry stakeholders in order to sustain the contribution of the species to the livelihoods of rural household